Physical and mechanical properties of pineapple bio-leather / Nurul Aliah Syahirah Norisam ... [et al.]. - Norisam, Nurul Aliah Syahirah; Shaharuddin, Putri Sofea; Kamal Azman, Anis Syazrina; Mat Sani, Fatin Nur’athirah; Nasir, Eryna (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Bio-leather, or vegan leather, is a range of materials that imitate the characteristics and look of regular animal leather but are crafted from eco-friendly and sustainable sources. These substances are frequently made with plant-derived components, agricultural leftovers, or advanced laboratory cultivation methods. However, the physical and mechanical properties of bio-leather made from pineapple skin fibre is yet to be explored. Therefore, the research objective of this study is to assess the material's tear resistance, stiffness, and ability to withstand water impact penetration. Various samples containing different amounts of pineapple skin fibre were created to investigate how it affects the quality of the bio-leather. In this research, pineapple skin, xanthan gum, cinnamon powder and lemon juice were used as the materials to create three samples with different weight of pineapple fibre. Specifically, 50g, 100g and 150g of pineapple skin were utilised, along with 30g of cinnamon powder, and 150ml of lemon juice for each sample. All samples were tested for flexibility, tensile strength and water impact penetration. It is found that the increasing amount of pineapple skin fibres in the leather increases the strength up to 167.26 N and reduces the water penetration by 44.54% with low flexibility.